Fruit traits diversity in Burmese grape through multivariate analysis. (5th November 2021) - Hoque, A. K. M. Ariful; Chowdhury, Hasina Tabassum; Tipu, Mohammad Monirul Hasan; Biswas, Suman; Islam, M R; Rahman, M. M.
Abstract: Burmese grape ( Baccaurea ramiflora Lour.) is a minor fruit plant grown in subtropical countries and is rich in different vitamins and minerals. In this study, fruit traits diversity of 23 Burmese grape accessions were assessed through multivariate analysis and application of covariance matrix in locating promising parents for an auspicious crossing program. Among the four clusters, assemblages III and VI dominated maximum number of fruit traits constitutions. Surrounded by the fruit traits constitution, the first principal axis largely affords 46.14% of the variation. Intergenotypic gap was observed highest (30.42) between the fruit traits constitution BS004 and BS019, followed by genetic constitution BS003 and BS004 (29.40). The maximum intracluster distance was noticed (40.50) for cluster IV, whereas cluster I showed the lowest intracluster distance (35.32). In between assemblages I and V, the highest interassemblage distance (835.77) was computed. On the other hand, the lowest distance (105.75) was computed between assemblages II and assemblage V. Observation indicated that higher intercluster differences were noticed than intracluster differences, and this recommended ample fruit traits variation among the fruit traits constitution of different clusters. With respect to both quantitative parameters' assemblage, CL004, CL010 from cluster I was quite diverse compared with all other assemblages, which is pertinent for a productive crossing program. Core Ideas: Genetic diversity of 23 Burmese grape genotypes were assessed by multivariate analysis. Cluster I (BS004 and BS010) was quite diverse compared with all other assemblages. Bulky fruit weight (20.4 g) and fruit yield per plant (60.7 kg) was highest in cluster I. The genotypes BS004 and BS010 were pertinent for a successful breeding program.